Street environment as public space in Kuala Lumpur: a case study of Jalan Masjid India / Normah Sulaiman - Sulaiman, Normah (2021)
In the history of urban development, roads have been an encouraging factor in shaping the physical form and fabric of a city for decades. It has brought many impacts and more challenges into urbanization affecting the overall urban quality of life. The research background is derived from issues regarding the impact of road design shaping the urban form towards urban liveability in Kuala Lumpur. Roads and streets are at the heart of our understanding in shaping the form and fabric of the city which the previous central idea is focusing on the movement of traffics. Streets have seen to renewed their importance in being expressive as a communication platform between human and their activity. Therefore, this research will focus on street functioning as an extension of space influencing social interaction and as a public space. The research aims to examine street strategy as a basis for informing street provision as a public space in terms of the street physical and social environment. The research questions and objectives are formulated to assist research in achieving this aim. The scope is set to study the physical and social dimension of the street environment. Supporting the research are the works of literature that expand understanding on key ideas of road and street as an infrastructural component constructing movements in the city. The literature also explores the concept of the street as a public space, street functions and typology. Next, the research examined the current street provision strategy and guidance and conduct a detailed review of street guide as public space from the universal and local context. The research methodology is formulated based on a method developed by Jahn Gehl that extensively focus on street transformations globally. Following this, a decision was taken to evaluate Jalan Masjid India, Kuala Lumpur. The rationale for choosing these streets was made based on the outcome of the pilot study testing the research methodology and instruments and the availability of variables for the study. The key findings from the survey highlighted the street as a robust connector for movement and the strength of the street is its connectivity despite the average street conditions to cater for all kinds of mobility and activities. The survey of the street social environment informs the street is an active space with multiple activities and social interactions taking places. Among other findings highlighted are street connectivity, quantity and quality of public space, street programme, street landscaping and street safety. The street social environment is robust but not a functional social interactions connector. The findings from both aspects are validated using the local and global street guidance which highlights what was lacking in the current street provision as a public space in Kuala Lumpur. Recommendations are drawn with a street strategy and a street as public space framework as a basis to inform improvements on current street provision influencing social interactions. Future research also suggests exploring the potential of the street as a healthy corridor in the city and developing collaborative guidelines contributing towards a better urban liveability and environment and increase general enjoyment of life for the public.